Pola Komunikasi Para Asatidzah dalam Menanamkan Nilai-Nilai Keislaman di Sekolah Dasar Quran Al Bayan Gunungtua - Raihan Abdul Halim; Malki Ahmad Nasir; Hendi Suhendi (UNISBA Press, 2024)
Abstract. This research studies the communication patterns of asatidzah in instilling Islamic values to students at the Al Bayan Quran Primary School, Gunungtua, Subang Regency. The writer uses a qualitative descriptive approach for this research by collecting data through observation, interviews and documentation. The results show that the Islamic values of students in the 6th grade at Al Bayan Primary School show a deep understanding that is not only theoretical. They live the teachings of Islam in their daily lives and actively participate in daily worships such as praying, reciting the Holy Qur’an, and dhikr. Their character development is strengthened through extracurricular activities of religious values, such as tahfidz Al-Qu’ran, group recitation, and social services. The communication patterns used by the Asatidzah are interpersonal and group communication in religious formation efforts. There are several supporting factors including an adequate worship facilities, the muhadharah programme, the Islamic educational background of the asatidzah, as well as their example in the practice of worship. However, there are several inhibiting factors such as the characteristics of students who are difficult to be managed, a busy extracurricular activities, lack of student awareness of order, the influence of the environment outside the school, and lack of parental involvement. In conclusion, the effective communication patterns are very important in instilling and strengthening Islamic values in students at the school. Abstrak. Penelitian ini mengkaji pola komunikasi para asatidzah dalam menyampaikan nilai-nilai keislaman kepada murid di Sekolah Dasar Quran Al Bayan, Gunungtua, Kabupaten Subang. Penelitian menggunakan pendekatan deskriptif kualitatif dengan mengumpulkan data melalui observasi, wawancara, dan dokumentasi. Hasilnya menunjukkan bahwa nilai-nilai keislaman siswa kelas 6 SDQ Al Bayan menunjukkan pemahaman mendalam yang tidak hanya teoritis. Mereka menghayati ajaran Islam dalam kehidupan sehari-hari, aktif berpartisipasi dalam ibadah harian seperti shalat, membaca Al-Qur'an, dan berdzikir. Pengembangan karakter mereka diperkuat melalui kegiatan ekstrakurikuler bernilai keagamaan, seperti tahfidz Al-Qur'an, pengajian kelompok, dan bakti sosial. Adapun pola komunkasi yang digunakan para asatidzah yaitu pola komunikasi antarpribadi dan kelompok dalam upaya pembinaan keagamaan. Ada beberapa faktor pendukung meliputi fasilitas ibadah yang memadai, program Muhadharah, latar belakang pendidikan islami para asatidzah, serta keteladanan mereka dalam praktik ibadah. Meskipun demikian, terdapat beberapa faktor penghambat seperti karakteristik siswa yang sulit diatur, kegiatan ekstrakurikuler yang padat, kurangnya kesadaran siswa terhadap keteraturan, pengaruh lingkungan luar sekolah, dan kurangnya keterlibatan orang tua. Kesimpulannya, pola komunikasi yang efektif sangat penting dalam menanamkan dan memperkuat nilai-nilai keislaman pada murid di sekolah tersebut.